2007
DOI: 10.1055/s-2007-970163
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Body Mass Index on Measured and Calculated Androgen Parameters in Adult Women with Hirsutism and PCOS

Abstract: There is growing evidence that obesity in women lead to a more severe form of hyperandrogenism and other endocrine abnormalities which may have some health implications later in life. Obese females are at higher risk for metabolic syndrome due to severe hyperandrogenemia. Calculated values for free testosterone are equivalent to those obtained by equilibrium dialysis, which is one of the reference measurement procedures (RMP) for estimation of free testosterone and may be capable of replacing values estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…These phenomena support the hypothesis that the definition of PCOS in the revised 2003 Rotterdam criteria identifies a different subset of women who have different endocrine profiles, whether they are hyperandrogenic or not. We recently reported that the BMI is associated with significantly lower SHBG levels in women with hirsutism and PCOS, resulting in significantly increased calculated free testosterone and FAI levels, which were appropriate markers for assessing hyperandrogenemia in these women (54,56).…”
Section: Discussionmentioning
confidence: 99%
“…These phenomena support the hypothesis that the definition of PCOS in the revised 2003 Rotterdam criteria identifies a different subset of women who have different endocrine profiles, whether they are hyperandrogenic or not. We recently reported that the BMI is associated with significantly lower SHBG levels in women with hirsutism and PCOS, resulting in significantly increased calculated free testosterone and FAI levels, which were appropriate markers for assessing hyperandrogenemia in these women (54,56).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in SHBG concentrations lead to an alteration of androgen and estrogen delivery to target tissues. Reduction of circulating SHBG determines an increase in the metabolic clearance rate of circulating SHBG-bound steroids, specifically testosterone, dihydrotestosterone, and androstenediol, the principal active metabolite of dihydrotestosterone [13]. This effect is compensated, however, by a consequent elevation of production rates.…”
Section: Commentsmentioning
confidence: 99%
“…Several studies suggest that adiposity is associated with hyperandrogenaemia [9][10][11], but this link between increasing BMI and hyperandrogenism may be mediated by insulin resistance [12]. There are studies that have failed to demonstrate a direct link between obesity and hyperandrogenism [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In brief, after the glucose and insulin levels had been measured, the following mathematical models were used to assess IR: the homeostatic model assessment of insulin resistance (HOMA-IR) (18), the quantitative insulin sensitivity check index (QUICKI) (19), and the insulin sensitivity index (ISI) (20,21). The defined cutoff points for the different insulin resistance indexes used were HOMA-IR R 2.5 (14,22), QUICKI % 0.33 (23,24), and ISI % 5 (25,26). Calculation of IR has been described in detail elsewhere (27).…”
Section: Assessment Of Ovulation Statusmentioning
confidence: 99%